Enhancing High School Students' Mathematical Problem-Solving Skills through Interactive Media: A Classroom Action Research Approach - Choirudin, Choirudin; Masuwd, Mowafg Abrahem; Lubis, Maesaroh (Journal of Teaching and Learning Mathematics, 2025)
To realize Indonesia Emas, where digitalization is prevalent across various fields today, it is essential to cultivate computational thinking skills through mathematics learning. This study evaluates the effectiveness of interactive media in enhancing mathematical problem-solving skills among senior high school students. Utilizing a Classroom Action Research (CAR) approach, 60 grade XII students from a high school in Jakarta participated in this research over one semester. Interactive media, including computer applications and educational games like "MathQuest" and "Puzzle Logic," were employed to make learning more engaging and challenging. Data collection methods included classroom observations, in-depth interviews with students and teachers, and analysis of pre- and post-intervention test results. The findings indicated a significant improvement in problem-solving skills, with a 25% increase in the average final test scores compared to initial tests. Additionally, 85% of students reported heightened motivation to learn. The study underscores the importance of integrating interactive media into mathematics teaching strategies to improve students' problem-solving abilities. It recommends incorporating technology into the learning process to maximize the academic potential of students. More research is suggested on the use of interactive media in mathematics learning to achieve innovative and optimal results.